How of COVID-19 Epidemic Spread and the effect of Heritance factor - Aburas, Omaro A.; Dhaw, Abtisam Miftah; Boras, Emhamed; Eljamay, Salwa Muftah; Elhsadi, Rabie A Ali (ITScience (Information Technology and Science), 2022)
This study focuses on to Coronavirus (COVID-19) as an epidemic disease, Aims to how can spread in Libya, Methods and Materials: 21 coronaviruses (COVID-19) patients the age range from 16 years to 72 years old found that incidence compared to the age group highest in age between 31-45 years and above, and the lowest percentage was in the immersive group between the age 16-30 years and less than 16 years and on another side, Results: found that the rate of spread rapid of the Coronavirus (COVID 19) in females is higher than that of males as the ratio 2:1, that 66.7% for females, and 33.3% for males. On the other hand, (CPR, and D-Dimer) are methods to detect cases of COVID-19, it found that 43% of patients with high CRP, while 57% of patients with normal CRP. The Dimer, nearly two-thirds 13 (61.9%) of the patients have normal D -dimer, while eight (38.1%) patients had high D –dimer, 24% of patients are admitted to the intensive care unit, while 76% of patients don’t admit to the intensive care unit. Conclusion: the relationship between viral infection and heritance also females are more exposed to infection than males. Knowledge of diagnostic tests for COVID-19 continues to evolve and, from one perspective, highlights the need for them for local validation of positive and negative Ct cutoff values when setting up RTq PCR tests for the detection of SARSCoV2